Pengaruh Harga, Pilihan Rasa, Dan Lokasi Terhadap Minat Beli - Melvin Reinaldi; Muhammad Fadilah; Rayhan Gunaningrat (STIKes Ibnu Sina Ajibarang, 2024)
This study conducts a thorough examination of the factors influencing consumer purchasing interest in the snack market, utilizing Mr. Fathoni Jr's Gajahan Leker as a case study. The research focuses on the analysis of the impact of price, flavor choices, and location on consumer purchasing preferences within the context of Leker products.By gathering data through surveys conducted using questionnaires and statistical analysis, the research discovers that the price of Mr. Fathoni Jr's Gajahan Leker plays a significant role in shaping consumer purchasing interest. Additionally, the various flavor choices offered by this brand also have a positive impact on purchasing preferences.The strategic placement and good accessibility of locations are proven to be key factors in attracting consumer purchasing interest. The success of Mr. Fathoni Jr's Gajahan Leker in leveraging strategically located sites to reach their target market contributes significantly to consumer purchasing interest.This study provides profound insights for business owners, marketers, and strategic decision-makers in the snack industry. By understanding the complex interactions between price, flavor choices, and location, Mr. Fathoni Jr can devise more effective strategies to enhance consumer purchasing interest, strengthen their brand, and support long-term business growth.